2020
DOI: 10.1088/2053-1591/ab9c5e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological properties of AA7075-T6 metal matrix composite reinforced with ceramic particles and aloevera ash via Friction stir processing

Abstract: Mechanical and wear properties of AA7075-T6 reinforced with SiC and Aloevera ash, fabricated using Friction stir processing (FSP) are investigated in this study. Due to less density, easy availability, and cost-effectiveness, aloevera ash is considered as one of the reinforcements. FSP is done using a square tool pin profile, at different tool rotational speeds. To study wear behaviour, pin on disc test is carried out on High Temperature Rotary Tribometer at 20N, 30N and 40N applied load. Wear increases on inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Similarly, 3 to 4 readings for each specimen were recorded and the specimen was changed. In tandem with the study by Tyagi et al (2020), the microhardness improved as the tool RPM was increased.…”
Section: Microhardness Testingmentioning
confidence: 61%
“…Similarly, 3 to 4 readings for each specimen were recorded and the specimen was changed. In tandem with the study by Tyagi et al (2020), the microhardness improved as the tool RPM was increased.…”
Section: Microhardness Testingmentioning
confidence: 61%
“…The mechanical properties of fabricated nano-ceramic surface composites on evaluation after one pass exhibited higher hardness, ultimate tensile strength, and finer grain structure in comparison to the base metal (BM). The fabrication of AA7075-T6 reinforced with SiC and Aloe vera ash, using FSP showed an improvement in wear and mechanical properties of all fabricated composite in comparison to the base metal [45]. Microhardness improved with the introduction of reinforcement.…”
Section: Surface Compositesmentioning
confidence: 93%
“…Many studies have been carried out on aluminum composites reinforced with various reinforcements. Tyagi et al 6 fabricated aluminum metal matrix composite (AMMC) reinforced with SiC and SiC + Aloe vera ash. They observed that the fabricated composite had better tensile properties than the matrix material.…”
Section: Introductionmentioning
confidence: 99%